Sepuluh Tahap Mewujudkan Kampung Mandiri Sampah: Ten Stages of Realizing a Trash Independent Village - Pajar Hatma Indra Jaya; Agung Prasetyo (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2022)
Most cities in Indonesia have trash problems. The local governments send the city's trash to the landfills. However, the longer the trash volume in the landfill is increasing, the fuller some landfills are going to be running out of space in a short time. Kampung Mandiri Sampah (The Independent Trash Village) is one of the city's solutions to reduce trash in the landfills. However, many people still have difficulties to create Kampung Mandiri Sampah. This paper aimed to provide a guideline regarding the stages of creating a Trash Independent Village with the trash donation method. To describe these stages, the Practicum Team of the Community Development Departement, Dakwah and Communication Faculty, UIN Sunan Kalijaga conducted an experiment to create a Trash Independent Village using participatory action research methods in Blimbingsari Hamlet, Caturtunggal Village, Depok Sub-district, Sleman District. It took six months. We conclude that there are ten stages that can be taken by the community to create a Trash Independent Village with the Trash Donation methods. The result of this program is to make household waste no longer disposed of in a landfill, but it is sorted and processed so that it provides economic benefits for the community. Kampung Mandiri Sampah sorts of waste from the house. The conclusion is that Kampung Mandiri Sampah is able to reduce the waste disposal volume in the landfill. ABSTRAK Hampir semua kota di Indonesia mempunyai masalah dengan sampah. Sampah kota dikirim ke Tempat Pembuangan Akhir (TPA). Namun semakin hari volume sampah di TPA semakin banyak sehingga beberapa TPA tidak lagi mampu menampung sampah. Kampung Mandiri Sampah merupakan salah satu solusi kota untuk mengurangi kecepatan penuhnya sampah di TPA. Namun banyak orang yang masih kesulitan untuk mewujudkan Kampung Mandiri Sampah. Tulisan ini bertujuan untuk memberikan guideline terkait tahapan mendirikan Kampung Mandiri Sampah dengan metode sedekah sampah. Metode yang digunakan adalah ceramah, focus group discussion, dan eksperimen dalam bentuk aksi bersama masyarakat Dusun Blimbingsari, Caturtunggal, Depok, Sleman. Kegiatan dilakukan oleh tim Praktikum Prodi Pengembangan Masyarakat, Fakultas Dakwah dan Komunikasi, UIN Sunan Kalijaga dengan memakan waktu enam bulan. Dari kegiatan tersebut disimpulkan terdapat sepuluh langkah yang dapat dilakukan oleh masyarakat untuk mewujudkan Kampung Mandiri Sampah metode sedekah sampah. Hasil program ini membuat sampah rumah tangga tidak lagi langsung di buang ke TPA, namun sampah dipilah dan diolah sehingga memberi manfaat ekonomi bagi masyarakat. Kampung Mandiri Sampah memilah sampah sejak dari rumah sehingga dapat disimpulkan bahwa adanya Kampung Mandiri Sampah mampu mengurangi volume pembuangan sampah ke TPA.